Concussion in sport - Return to sports following concussion - Mona, D. (Schweizerische Zeitschrift für Sportmedizin und Sporttraumatologie, 2005)
The diagnosis and management of concussion during sports activity is since years one of the most challenging endeavours for all sports physician working on the field. In the last years, more than 20 management guidelines regarding return to play issues have been published. Current research has prompted a revaluation and revision of prior guidelines with the aim to create an «unité de doctrine» in concussion management strategies. Two International Symposia on Concussion in Sport, in Vienna 2001 and in Prague 2004, were organised by the International Ice Hockey Federation (IIHF), the Fédération Internationale de Football Association Medical Assessment and Research Centre (FIFA, F-MARC), and the International Olympic Committee Medical Commission (IOC). The experts group of these two Concussion Symposia pointed out some important recommendations of return of sports following concussion which are discussed in this Current Concept paper. Definition of concussion has changed, on-field examination has been shown to be difficult but crucial, and serial follow-up controls are mandatory to precisely evaluate the severity of the lesion. Based upon a scale of postconcussion symptoms, precise return to play recommendations have been defined and should be known by all physicians involved in speed and contact sports.